Mediated and Discursive Readings of Argentine, American and Mexican Female Academics in the Coverage of Female Presidential Candidates - Alvarez Monsiváis, Edrei (Universidad de Guadalajara. Departamento de Estudios de la Comunicación Social., 2022)
In the present study, ten focused interviews were conducted where female university professors from Argentina, the United States and Mexico read news articles in newspapers about Cristina Fernández, Hillary Clinton and Margarita Zavala, respectively. Seven ways in which journalistic messages were stylistically and discursively deconstructed were found, among which are the questioning of editorial decisions, as well as evidencing how the ideology of the newspaper generated a specific treatment with the intention of manipulating audiences.